Nurses' Kangaroo Mother Care practice implementation and future challenges: an integrative review. Issue 2 (27th October 2019) - Maniago, Jestoni D.; Almazan, Joseph U.; Albougami, Abdulrhman S.
Abstract : Background: Nurses play a crucial role in Kangaroo Mother Care practice, but their application in specific policies and practices involves challenges. A comprehensive literature review is needed to improve understanding of specific barriers that are most relevant to nurses and the improvement of this practice. This review investigates nurses' barriers in implementing Kangaroo Mother Care, in order to illustrate directions for future research. Methods: This study was based on integrative review method and exploring nurses' barriers in implementing Kangaroo Mother Care, strategies to reduce its barriers. CINAHL, Medline, Web of Science, ProQuest Nursing and Allied Health Database, PubMed and Science Direct Taylor & Francis databases were searched for the following: (i) studies with no year restrictions, (ii) peer‐reviewed journal articles, (iii) original research and (iv) articles written in English. Each article was appraised for methodological validity review using critical appraisal checklist. Results: The search revealed 19 articles from diverse countries. Four main themes were generated from the synthesis of the findings: (i) barriers related to nurses' perspective and emotion towards KMC, (ii) healthcare institution barriers towards KMC, (iii) barriers related to parental experience in providing KMC and (iv) strategy to improve KMC implementation. Conclusions: Nurses experience several barriers in successfully implementing KMC in healthcare settings. This review reported strategies to reduce KMC barriers and to improve its utilisation in healthcare settings. Hospitals should establish adequate manpower, clear guidelines, sufficient supplies and equipment, capacity building among staff and proper Kangaroo Mother Care information dissemination for patients.